Pupuk Organik Padat dari Eceng Gondok, Kotoran Sapi, dan Dedak Padi dengan Effective Microorganisme 4 (EM4) - Sri Widyastuti; Risa Suryananta Arfa (Department of Environmental engineering, Faculty of Science and Technology, Islamic State University Sunan Ampel Surabaya, 2021)
Water hyacinth (Eichonia crassipes) is one type of aquatic plant that has a fast growth rate. As a result, sunlight is blocked from entering the water, so that aquatic biota cannot carry out the photosynthesis process perfectly. This study aims to determine the value of C/N ratio, levels of Phosphorus (P), Potassium (K), pH, and temperature (T) in composting for 16 days with the addition of 200 mL of bioactivator effective microorganism 4 (EM4) in each reactor. Variations of raw materials used are Control Reactor (RK) containing 1.5 kg of water hyacinth; Treatment Reactor 1 (R1) contains 0.5 kg of water hyacinth + 1 kg of cow dung; Treatment Reactor 2 (R2) contains 0.5 kg of water hyacinth + 1 kg of rice bran; and Treatment Reactor 3 (R3) contains 0.5 kg of water hyacinth + 1 kg of cow dung + 1 kg of rice bran. The results showed that the combination of raw materials had an effect on the quality of the organic fertilizer produced. The combination of Treatment 3 (R3) produced organic fertilizer with the best quality, namely C/N ratio = 15.30%, pH = 7.16, macronutrient P = 4.91% and K = 8.36% which met the quality standard requirements. Minister of Agriculture Number 261/KPTS/SR.310/M/4/2019 concerning the minimum technical requirements for organic fertilizers, biological fertilizers, and soil improvement.